Organizational Factors of Environmental Sustainability Implementation: An Empirical Analysis of US Cities and Counties. Issue 4 (7th August 2016) - Laurian, Lucie; Crawford, Jan
Abstract: Environmental sustainability goals are increasingly embedded in local planning, but implementation proves difficult. Using a survey of 217 planners working in a random sample of 146 small to mid-sized American cities and counties, we identify the organizational factors that support and hinder the implementation of environmentally sustainable practices. The analysis is based on a conceptual framework that encompasses organizational capacity, culture, structure, participatory decision-making, the framing of sustainability and contextual factors. We find that environmental sustainability implementation is lagging (although cities are generally ahead compared to counties) and that outcome evaluation is rare, precluding adaptive learning. The major barrier to implementation is that sustainability is low on political and managerial agendas. As expected, local public support, innovation-supportive organizational culture and the prioritization and framing of environmental sustainability support implementation. Surprisingly, innovation diffusion does not occur across neighbouring localities, local capacity and public participation are irrelevant for implementation and hierarchical rather than integrated institutional structures support implementation.